Terrorism, peace and conflict studies investigating the crossroad - Toros, Harmonie 1974-; Tellidis, Ioannis (Routledge, 2014)
The book can be described as an important and an informative text book. It is composed of 12 research articles on Terrorism Studies. The introductory article by the editors on bridging the gap between Peace and Conflict Studies and Terrorism studies sets the tone for the rest of the book